Numerical Analysis of Soil Slope Stabilization by Soil Nailing Technique - Mangnejo, D. A.; Oad, S. J.; Kalhoro, S. A.; Ahmed, S.; Laghari, F. H.; Siyal, Z. A (Engineering, Technology & Applied Science Research, 2019)
Slope instability may be a result of change in stress conditions, rise in groundwater table and rainfall. Similarly, many slopes that have been stable for several years can abruptly fail due to changes in geometry, weak soil shear strength or as the effect of an external force. Debris flows (i.e. slope failures) take place without any warning and can have devastating results. So, it is vital to understand the slope failure mechanism and adopt safety prevention measures. Soil nailing is one of the widely used stabilization techniques for soil slopes. In this study, soil nail technique is proposed to upgrade the existing slope in clay. A parametric study was conducted to understand the effects of different nail diameter (i.e. 25mm and 40mm) and nail inclination (i.e. 200, 250, 300, 350 and 400) on slope stability. Morgenstern-Price (i.e. limit equilibrium) method was used to determine the factor of safety of the slope. It was found that the factor of safety of the existing slope improved significantly with three rows of 40mm diameter nail at an inclination of 400.